Teaching practices in Grade 5 mathematics classrooms with high-achieving English learner students. Issue 1 (2nd January 2017) - Merritt, Eileen G.; Palacios, Natalia; Banse, Holland; Rimm-Kaufman, Sara E.; Leis, Micela
ABSTRACT: Teachers need more clarity about effective teaching practices as they strive to help their low-achieving students understand mathematics. Our study describes the instructional practices used by two teachers who, by value-added metrics, would be considered "highly effective teachers" in classrooms with a majority of students who were English learners. We used quantitative data to select two fifth-grade classrooms where students, on average, made large gains on a mathematics achievement test, and then examined teaching practices and contextual factors present in each classroom. Participants included two teachers from a mid-Atlantic district and their students who were 67% English learners and 68% economically disadvantaged. We found that the use of multiple representations of mathematics concepts, attention to vocabulary building, individual and group checks for understanding and error analysis were prevalent practices in both high gains classrooms. Also, class sizes ranged from 12–19 students. Discussion focuses on whether observed practices are aligned with recommended teaching practices for English learner students.